Synthesis, Characterization and Biological Evaluation of Some New Oxino bis-Pyrazole Derivatives - Ghafoor, Abdul; Aslam, Noreen; Elliott, Mark C.; Sajid, Naveed; Nasrullah, Muhammad; Ashraf, Muhammad; Qurat-ul-Ain; Khan, Misbahul Ain (Asian Journal of Chemistry, 2016)
Novel oxino bis-pyrazoles were obtained by two step reactions of 3-methyl-1-phenyl pyrazoline-5-one, cyanoacetamide and aryl- or alkylaldehydes, in the presence of catalytic amounts of triethylamine and ethanol as a solvent. All the synthesized compounds were evaluated for their inhibitory activities against butyrylcholinesterase (BChE) and bovine a-chymotrypsin. Two compounds, 8 and 9 were found to be good inhibitors of enzyme BChE with IC50 values of 52.74 ± 0.006 and 51.85 ± 0.005 μM, respectively.